Why justice fails - Seymour, Whitney N. (New York William Morrow and Company, Inc., 1973)
In this enourmously readable, provocative book, the author put his commitment on the line. He vividly describes where injustice ends: With a young first offender flung into jail with hardened criminals who tutor him in a life of crime.
Keywords: Law